Epilithic organisms in Priabonian marls with pillow lavas of Euganean Hills (NE Italy) - Massari, Francesco; Dieni, Iginio; Agnini, Claudia (Journal of Mediterranean Earth Sciences, 2020)
Abstract In the Castelnuovo area of the Euganean Hills upper Priabonian marls (referred to as Brendola Marl) are associated with products of submarine basaltic eruptions, including pillow lavas and lava flows, pertaining to the first, late Eocene volcanic phase in the district. A biostratigraphic revision of the marl by means of the calcareous nannofossils allowed to ascribe the succession to the Priabonian Zone CNE19 (Agnini et al., 2014). The planktonic foraminiferal content indicates the upper part of Zone E15 with an estimated age of 35.3-34.3 Ma (Berggren and Pearson, 2005). The benthic foraminiferal assemblage was examined to provide a palaeodepth estimation, which suggests a deep neritic environment. A reconstruction of the late Priabonian events occurred in the study area led to identify various episodes of submarine eruptive activity with formation of pillows and associated hyaloclastic material, alternated with phases of colonization of the upper parts of the pillows and larger hyaloclasts by epilithic and vagile organisms such as crinoids, cirripeds, brachiopods and cidarid echinoids, followed by their post-mortem disaggregation, dispersal and eventual burial due to the marl sedimentation. These episodes were closed by the emplacement of a lava flow, whose flat top was colonized only by sparse cirripeds.